(untitled) (Research, Society and Development, 2021)
There is a great concern with a healthier lifestyle for an increasing number of individuals, which is reflected in an increase in life expectancy. In this context, vitamin supplements and enriched foods appear as practical possibilities for nutritional enhancers. Spirulina Platensis has a high concentration of nutrients and is one of the most complete natural supplements available in nature. Thus, the production of a food with good acceptability, such as jelly, appears as an alternative to supplement Spirulina, given that the smell and strong color of its unprocessed form often hinder its use in food. For this purpose, a mint jelly enriched with Spirulina (Spirulina platensis) in different formulations was prepared in the present study. In order to verify the formulations, physical-chemical tests (water content and its activity, ashes, soluble solids, protein and acidity) and microbiological tests were carried out, the latter followed the recommendations of current legislation. The physical-chemical characteristics were shown to conform to the standards established by the legislation, a factor that contributes to the formation of pleasant and desirable sensory aspects, making the jelly viable for consumption. Positive results were also obtained in microbiological studies, where the results were within the appropriate parameters, showing the quality of the jellies, the raw material and the production process. In view of such data, it can be concluded that the jelly in this study has a high nutritional content, and may in the future become a great help in the nutritional supplementation of the population.